2021
DOI: 10.33393/dti.2021.2342
|View full text |Cite
|
Sign up to set email alerts
|

The role of patient preferences in adherence to treatment in chronic disease: a narrative review

Abstract: Adherence to prescribed medication is important to the management of all diseases, especially those of chronic nature. Drug effectiveness is substantially compromised by therapy nonadherence. We reviewed the available evidences on the impact of patient preferences for therapy on adherence to a prescribed treatment in chronic diseases requiring long-term treatment. A search on PubMed retrieved 699 publications, leading to a selection of 12 publications: 6 on osteoporosis, 2 on moderate-to-severe asthma, 1 on ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…[ 10 ] Because these patients are likely suffering from chronic (e.g., kidney disease) or other severe conditions (e.g., cancer), they may be more vulnerable to needle phobia and its impacts on treatment adherence. Avoidance behavior may have a more significant impact on patients with conditions requiring frequent injections compared to healthier individuals [ 43 ]. In fact, literature reports adverse health outcomes and increased mortality in type II diabetes and hypertension patients with poor treatment adherence, which typically comprises frequent injections and blood draws [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] Because these patients are likely suffering from chronic (e.g., kidney disease) or other severe conditions (e.g., cancer), they may be more vulnerable to needle phobia and its impacts on treatment adherence. Avoidance behavior may have a more significant impact on patients with conditions requiring frequent injections compared to healthier individuals [ 43 ]. In fact, literature reports adverse health outcomes and increased mortality in type II diabetes and hypertension patients with poor treatment adherence, which typically comprises frequent injections and blood draws [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance behavior may have a more significant impact on patients with conditions requiring frequent injections compared to healthier individuals [ 43 ]. In fact, literature reports adverse health outcomes and increased mortality in type II diabetes and hypertension patients with poor treatment adherence, which typically comprises frequent injections and blood draws [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an understanding of patient views and preferences is essential to enhance their participation, adherence, and satisfaction with treatment. 31 , 38 , 45 The important attributes identified by this systematic review will inform the design of future DCE and other studies aiming to determine patient preferences for various nonsurgical treatments for value-based care in patients with CMP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients more preferably use oral pharmacotherapy [ 46 , 47 , 48 ]. Therefore, the level of adherence among patients taking oral drugs is higher than those taking injectable drugs.…”
Section: Discussionmentioning
confidence: 99%